Perception of the olympic values in the portuguese coaches of individual and team sports - Rocha, T. C.; Mateos-Padorno, C.; Fuentes-García, J. P.; González-Silva, J.; Martínez-Patiño, M. J. (Journal of Human Sport & Exercise, 2023)
The aim of this study has been to analyse the perception of the Olympic values shown by coaches of different levels and categories in Portugal related to the type of sport they train (individual or collective). The study sample consisted of 1473 Portuguese coaches (214 female and 1259 male) from 34 different sports modalities (individual and collective). The data collection instrument was a three-dimensional questionnaire (perception of the Olympic Symbols, opinion about participation in the Olympic Games and values related to the Olympic Games). Descriptive analysis showed differences between the opinions of individual and team sports coaches in the three dimensions. The inferential analysis only showed significant differences in the dimension of opinion about participation in the Olympic games. These results reveal the difference in the perception of the Olympic values between coaches of individual sports and those of team sports.